Review on the Toxicity and Safety of Medicinal Plants during Pregnancy - Aniket Rajesing Girase; Javesh Kashinath Patil; Devshree Yashwantbhai Patel; Harsha Vasudev Chaudhari; Sachinkumar Madhukar Mahajan (Proceedings, 2024)
Introduction: Although herbs are widely used and considered safe, they can be toxic, especially during pregnancy [...]